Evaluation of oxidant-antioxidant status in tissue samples in oral cancer: A case control study - Kumar Chandan Srivastava; Ravi David Austin; Deepti Shrivastava (Wolters Kluwer Medknow Publications, 2016)
Background: Imbalances between the oxidant-antioxidant status have been implicated in the pathogenesis of several diseases, including cancer. The aim of this study was to evaluate the extent of lipid peroxidation and antioxidants in the tissue samples of oral squamous cell carcinoma (OSCC) patients of different clinical stages in comparison with the healthy controls. Materials and Methods: A case-control study was designed with 20 new histopathologically proven oral carcinoma patients and an equal number of age, sex, and tobacco chewing habit matched healthy subjects. Their tissue samples were subjected to evaluation of lipid peroxidation product and antioxidant enzymes, namely, superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and glutathione peroxidase (GPx) using spectrophotometric methods. The data are expressed as mean ΁ standard deviation. The statistical comparisons between the study groups were performed by independent Student's unpaired t-test and one-way analysis of variance. Post-hoc analysis was performed for within study group comparisons. Karl Pearson correlation was performed for the biochemical parameters within the group and between the groups. For statistically significant correlations, simple linear regression was performed using SPSS (α=0.05). Results: Significant reduction in lipid peroxidation (P < 0.001) SOD and CAT (P < 0.001) was observed in the tissue of OSCC patients as compared with the healthy controls. On the other hand, reduced GSH and GPx were significantly increased in tumor samples. Conclusion: Reduced lipid peroxidation and increased activity of reduced GSH and GPx provides the suitable environment for the local growth and invasion of the tumor and metastasis in the later stages. Among the antioxidant enzymes, GSH reductase appears to have a profound role in carcinogenesis and thus it can be considered as potential prognostic marker.